Non-trivial surface states of samarium hexaboride at the (111) surface - Yoshiyuki Ohtsubo (Nature Portfolio, 2019)
Samarium hexaboride has unusual electronic properties that have been suggested to arise from topological effects. Here the authors present spin-resolved ARPES measurements of the (111) surface and observe surface states that may give insight into the bulk topological properties.